Intravascular large B-cell lymphoma as a covert trigger for hemophagocytic lymphohistiocytosis complicated with capillary leak syndrome: a case report and literature review - Wen, Jingjing; Xu, Juan; Ji, Jie; Zhang, Wenyan; Zheng, Qin; Liu, Ting; Zheng, Yuhuan; Ma, Hongbing (Frontiers in Immunology, 2024)
Intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of non-Hodgkin lymphoma. Patients with hemophagocytic lymphohistiocytosis (HLH)-associated IVLBCL variants exhibit significantly poor survival. Cytokines play pivotal roles in malignancy-associated HLH as well as in capillary leak syndrome (CLS). The pathogenesis of CLS involves hyperpermeability and transient endothelial dysfunction. Here, we report the first case of HLH-associated IVLBCL variant complicated with CLS. The patient presented with fever, refractory hypoproteinaemia, hypotension and severe edema, followed by telangiectasias. Treatment with etoposide and dexamethasone and hydroxyethyl starch-based artificial colloid led to transient improvement. The diagnosis of IVLBCL was confirmed after the sixth bone marrow biopsy. Subsequently, theR-CHOP (rituximab, cyclophosphamide, hydroxydaunorubicin, vincristine, and prednisolone) regimen was administered and resulted in prompt alleviation of CLS and HLH symptoms. The patient has survived for more than 6 years after combination of immunochemotherapy and autologous peripheral stem-cell transplantation. This case provides some insights into the mechanism and clinical management of IVLBCL complicated with HLH and CLS.Similar cases concerning lymphoma-associated CLSs were also reviewed.